Increasing utilization of urethroplasty for male urethral stricture disease: analysis of in-hospital interventions in Germany from 2006 to 2023 - Herout, Roman; Flegar, Luka; Zähringer, Juliane; Eisenmenger, Nicole; Huber, Johannes; Thomas, Christian; Baunacke, Martin (International urology and nephrology, 2025)
There is a wide range of surgical treatments for urethral strictures. There is no information on the extent to which these procedures have been used over the past few years.